Matrix sublimation/recrystallization for imaging proteins by mass spectrometry at high spatial resolution - Yang, Junhai; Caprioli, Richard M (Analytical chemistry (Washington), 2011)
We have employed matrix deposition by sublimation for protein image analysis on tissue sections using a hydration/recrystallization process that produces high-quality MALDI mass spectra and high-spatial-resolution ion images. We systematically investigated different washing protocols, the effect of tissue section thickness, the amount of sublimated matrix per unit area, and different recrystallization conditions. The results show that an organic solvent rinse followed by ethanol/water rinses substantially increased sensitivity for the detection of proteins. Both the thickness of the tissue section and the amount of sinapinic acid sublimated per unit area have optimal ranges for maximal protein signal intensity. Ion images of mouse and rat brain sections at 50, 20, and 10 μm spatial resolution are presented and are correlated with hematoxylin and eosin (H&E)-stained optical images. For targeted analysis, histology-directed imaging can be performed using this protocol where MS analysis and H&E staining are performed on the same section.